Arthroscopic patellar denervation with microfracture for treating patellofemoral arthritis in cold weather conditions: a retrospective clinical analysis - Ma Xinnan; Zhang Xin; Ma Yingkai; Zhao Yonghou; Liu Kai (Frigid Zone Medicine)
To evaluate the clinical efficacy of combining arthroscopic patellar denervation with microfracture in the treatment of patellofemoral arthritis under cold weather conditions.